RECONSTRUCTION OF WOMENS SOCIAL MODALITIES IN TALING CUSTOMS: Cultural Strategies in Policies to Combat Stunting in East Flores - Kosat, Emanuel; Pantola, Bruno Rey Sonby; Lamawuran, Yosef Dionisius; Susu, Mikael (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
This study aims to analyze how the Taling customary practice, carried out by Lamaholot women, can be reconstructed as a cultural strategy in stunting prevention policies in East Flores Regency. Using a qualitative approach and ethnographic methods, this study positions Taling as a social modality for women that has not been accommodated in formal policy design but functions effectively in maintaining food security and community solidarity. The Longwe women's empowerment framework was used to evaluate the extent to which indigenous women achieved the five dimensions of empowerment: welfare, access to resources, critical awareness, participation, and control in the local development process. The research was conducted in five villages within Witihama Sub-district, utilizing participatory observation, in-depth interviews, focus group discussions, and documentary studies. The findings show that the local value-based food redistribution system in Taling practice effectively strengthens women's leadership, builds social trust, and creates distribution mechanisms that are responsive to the needs of vulnerable households. However, this social power has not been recognized in the framework of stunting prevention policies, which are still dominated by a technocratic approach. These findings emphasize the importance of integrating social and community structures into local public policy through participatory, adaptive, and culturally based governance models.gb777